Mathematical analysis of single queue multi server and multi queue multi server queuing models: comparison study - Prasad, Vijay; V.H, Badshah; Koka, Tariq Ahmad (Global Journal of Mathematical Analysis, 2015)
In the research paper entitled Mathematical Analysis of Single Queue Multi Server and Multi Queue Multi Server Queuing Model, Prasad and Badshah [7] were proved that single queue multi server model is better than multi queue multi server model, and discussed the relation between the performance measures of these two models, and derive the mathematical equations. In this paper we derive the total cost with assumption of certain Waiting cost in both cases. Also, prove that the expected total cost is less for single queue multi server model as comparing with multi queue multi server model.